Study of low speed flow cytometry for diffraction imaging with different chamber and nozzle designs. Issue 11 (9th July 2013) - Sa, Yu; Feng, Yuanming; Jacobs, Kenneth M.; Yang, Jun; Pan, Ran; Gkigkitzis, Ioannis; Lu, Jun Q.; Hu, Xin‐Hua
Abstract Achieving effective hydrodynamic focusing and flow stability at low speed presents a challenging design task in flow cytometry for studying phenomena such as cell adhesion and diffraction imaging of cells with low‐cost cameras. We have developed different designs of flow chamber and sheath nozzle to accomplish the above goal. A 3D computational model of the chambers has been established to simulate the fluid dynamics in different chamber designs and measurements have been performed to determine the velocity and size distributions of the core fluid from the nozzle. Comparison of the simulation data with experimental results shows good agreement. With the computational model significant insights were gained for optimization of the chamber design and improvement of the cell positioning accuracy for study of slow moving cells. The benefit of low flow speed has been demonstrated also by reduced blurring in the diffraction images of single cells. Based on these results, we concluded that the new designs of chamber and sheath nozzle produce stable hydrodynamic focusing of the core fluid at low speed and allow detailed study of cellular morphology under various rheological conditions using the diffraction imaging method. © 2013 International Society for Advancement of Cytometry